Pancreatic islet-autonomous insulin and smoothened-mediated signalling modulate identity changes of glucagon+ α-cells. Issue 11 (November 2018) - Cigliola, Valentina; Ghila, Luiza; Thorel, Fabrizio; Gurp, Léon; Baronnier, Delphine; Oropeza, Daniel; Gupta, Simone; Miyatsuka, Takeshi; Kaneto, Hideaki; Magnuson, Mark; Osipovich, Anna; Sander, Maike; et al.
Abstract The mechanisms that restrict regeneration and maintain cell identity following injury are poorly characterized in higher vertebrates. Following β-cell loss, 1–2% of the glucagon-producing α-cells spontaneously engage in insulin production in mice. Here we explore the mechanisms inhibiting α-cell plasticity. We show that adaptive α-cell identity changes are constrained by intra-islet insulin- and Smoothened-mediated signalling, among others. The combination of β-cell loss or insulin-signalling inhibition, with Smoothened inactivation in α- or δ-cells, stimulates insulin production in more α-cells. These findings suggest that the removal of constitutive 'brake signals' is crucial to neutralize the refractoriness to adaptive cell-fate changes. It appears that the maintenance of cell identity is an active process mediated by repressive signals, which are released by neighbouring cells and curb an intrinsic trend of differentiated cells to change. Cigliola et al. show that β-cell loss activates insulin production in a small number of α-cells and that insulin and Hedgehog signalling actively maintain and enforce the α-cell fate.